Optimalisasi Digitalisasi Marketing di Padukuhan Pancoh - Ghiffara, Mustafad; Prasetya, Gede Guruh; Fathurrohman, Rofi; Ernanda, M. Ricki Bagus; Puspaningrum, Rosita; Azizah, Wardah Ma’rifatul; Mian, Margareta Angelina; Almi, Nuraisyah Ayumi; Putra, M. Rahman Alin; Hidayat, Qoori; Kusumawati, Rita (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
The Community Service Program (PKM) is a form of student service to the community as an implementation of the Tridharma of Higher Education. PKM 194 of Universitas Muhammadiyah Yogyakarta (UMY) which was placed in Dusun Pancoh, Kelurahan Girikerto, Kecamatan Turi, Sleman, which had problems in empowering Micro, Small, and Medium Enterprises (MSMEs) through digital marketing to increase their business competitiveness. The purpose of this program is to improve the understanding, skills, and independence of MSME actors in utilizing digital media as a means of product marketing, so that they can expand the market and increase business competitiveness. The methods used include digital marketing socialization and training, assistance in creating social media content, product photography, compiling digital catalogs, to creating Linktree as a liaison for various business platforms. The results of this activity showed high enthusiasm from MSME actors, although most still use traditional marketing methods. One of the MSMEs assisted, namely Viva Nafigo, succeeded in implementing a digital marketing strategy by improving the quality of product photos, optimizing Instagram accounts, and creating catalogs and Linktrees to facilitate customer access. Although this program has a positive impact, there are several obstacles faced, such as the limited number of MSMEs and the short mentoring time. The implementation of marketing digitalization requires a continuous process in order to provide optimal results. Therefore, further efforts and continuous support are needed to ensure the success of MSME digitalization in Dusun Pancoh